Measuring Positive Childhood Experiences: Testing the Structural and Predictive Validity of the Health Outcomes From Positive Experiences (HOPE) Framework - Guo, Shuaijun; O'Connor, Meredith; Mensah, Fiona; Olsson, Craig A.; Goldfeld, Sharon; Lacey, Rebecca E.; Slopen, Natalie; Thurber, Katherine A.; Priest, Naomi (Academic pediatrics, 2022)
Positive childhood experiences (PCEs), that occur within secure and nurturing social environments, are fundamental to healthy physical, social-emotional, and cognitive development. However, reliable measures of these experiences are not yet widely available. We used data from the Longitudinal Study of Australian Children (LSAC) to empirically represent and psychometrically evaluate 3 primary domains of PCEs defined within the Health Outcomes from Positive Experiences (HOPE) framework, specifically: 1) nurturing and supportive relationships; 2) safe and protective environments and; 3) constructive social engagement and connectedness. LSAC is a nationally representative cohort that has followed young Australians from birth since 2004. LSAC data were used to represent the 3 primary HOPE-PCEs domains (birth to 11 years) across 4 inter-related PCEs constructs: 1) positive parenting, 2) trusting and supportive relationships, 3) supportive neighborhood and home learning environments, and 4) social engagement and enjoyment. Confirmatory factor analysis was used to test the proposed 4-factor structure. Predictive validity was examined through associations with mental health problems and academic difficulties at 14 to 15 years. The 4-factor structure was supported by empirical data at each time point. Higher exposure to PCEs across each domain was associated with lower reporting of mental health problems (β = −0.20 to −2.05) and academic difficulties (β = −0.01 to −0.13) in adolescence. The 4 LSAC-based HOPE-PCEs have sufficient internal coherence and predictive validity to offer a potentially useful way of conceptualizing and measuring PCEs in future cohort studies and intervention trials aiming to enhance the understanding of, and mitigate the negative impacts of, adverse childhood experiences.